2014
DOI: 10.1021/am5013134
|View full text |Cite
|
Sign up to set email alerts
|

Digital Memory Versatility of Fully π-Conjugated Donor–Acceptor Hybrid Polymers

Abstract: The fully π-conjugated donor-acceptor hybrid polymers Fl-TPA, Fl-TPA-TCNE, and Fl-TPA-TCNQ, which are composed of fluorene (Fl), triphenylamine (TPA), dimethylphenylamine, alkyne, alkyne-tetracyanoethylene (TCNE) adduct, and alkyne-7,7,8,8-tetracyanoquinodimethane (TCNQ) adduct, were synthesized. These polymers are completely amorphous in the solid film state and thermally stable up to 291-409 °C. Their molecular orbital levels and band gaps vary with their compositions. The TCNE and TCNQ units, despite their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 75 publications
1
35
0
1
Order By: Relevance
“…Yet, the negative ESP regions (in blue A and B) arisen from the pyrazine and benzothiadiazole (BT) also exist. These negative regions could act as “trap” sites to impede the field‐induced transfer of charge carriers . Under a low voltage bias, charge carriers hardly get enough energy to overcome the injection barriers between the donor and acceptors.…”
Section: Methodssupporting
confidence: 53%
“…Yet, the negative ESP regions (in blue A and B) arisen from the pyrazine and benzothiadiazole (BT) also exist. These negative regions could act as “trap” sites to impede the field‐induced transfer of charge carriers . Under a low voltage bias, charge carriers hardly get enough energy to overcome the injection barriers between the donor and acceptors.…”
Section: Methodssupporting
confidence: 53%
“…Thef irst reduction potential (E red,1 )o rthe LUMO energy level decreased as more TCNE was added ( Figure 13). [113] Thes ame polymer could also be postfunctionalized by aC A-RE reaction with TCNQ to yield P16 ( Figure 14). This finding was strongly associated with device performances.B ottom-gate top-contact-type thin-film transistors (TFTs) based on P14 and P15 were fabricated and their performances were evaluated.…”
Section: Low-bandgap Semiconducting Polymers By Ca-re Click Postfuncmentioning
confidence: 99%
“…[14] Yamashita and co-workers reported that alkyne derivatives with a1 ,3-dithiol-2-ylidene moiety reactedw ith TCNE to give TCBD derivatives that showed amphoteric redox behavior in cyclic voltammetry (CV). [17] They also investigated their applicationsa si on sensors using polymere ffects, digitalm emory, [18] and photovoltaic devices. [16] Michinobu et al demonstrated that polymers embedded with TCBD units showeda nI CT absorption band with al ow energy band gap.…”
Section: Synthesis Of Tcbd Derivativesmentioning
confidence: 99%